Kajian Penyiaran Secara Ilegal Perspektif Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Cristy, Michele Angeline; Saly, Jeane Neltje (Syntax Corporation, 2023)
This research delves into the study of illegal broadcasting from the perspective of Law Number 28 of 2014 concerning Copyright. The background of the research arises from the increasing cases of copyright violations through unauthorized broadcasting media, which has the potential to harm the intellectual property owners. The objective of this research is to analyze the impact and legal implications of illegal broadcasting practices within the framework of the prevailing copyright law. The research method involves legal document analysis, literature review, and case studies to gather up-to-date information. The research findings indicate that illegal broadcasting practices harm copyright holders, create injustice in the creative industry, and violate legal norms governing copyright. The legal implications include sanctions that can be applied to illegal broadcasting actors in accordance with the provisions of the Copyright Law. The research conclusion emphasizes the need for stricter law enforcement and preventive measures to address illegal broadcasting in order to protect copyright and promote sustainable growth in the creative industry. This study provides in-depth insights into the legal aspects of illegal broadcasting, summarizes the complexity of the issue, and highlights the serious attention required for copyright protection in the digital era.Illegal Broadcasting; Copyright Law; Legal Perspective